Urban governance and solid household waste management in Togo: Case of the town of Vogan in Togo (West Africa) - Holaly, Gbekley Efui; Ablam, NYAKPO; Djiwonou, ADJALO Koffi; Hanou, GBEKLEY Abla -Sika; Tchadjobo, TCHACONDO (Edelweiss Applied Science and Technology, 2024)
The regular growth of the population and the change in consumption patterns lead to significant production of urban waste, the management of which is becoming an environmental concern. The rapid population growth and changing consumption patterns have led to significant urban waste production, making waste management a pressing environmental concern. This study aims to improve solid household waste management in Vogan through a diagnostic analysis. Conducted from June to August 2022, the cross-sectional study surveyed household knowledge, attitudes, and practices related to waste management. Data were collected through an opinion survey of 350 households across 20 districts, using semi-structured questionnaires, interviews, and field observations. Additionally, heavy metal content in waste samples was analyzed in the laboratory. Results showed that 85.43% of households had trash cans, yet 62.26% disposed of their waste in illegal dumpsites due to a lack of pre-collection services. Furthermore, 10.57% used waste as backfill in streets. Knowledge about waste management was moderate, with 62.29% having heard of it, and 70% of these respondents recognizing the importance of subscribing to a pre-collection service. Laboratory analyses revealed contamination of a landfill with cadmium, lead, and copper, along with widespread zinc pollution across all selected sites. Raising awareness and installing proper waste management infrastructure are critical to improving public health and enhancing the town's environmental quality.